Corporate growth through mergers and acquisitions: Viable strategy or road to ruin? - P. Brews (South African Journal of Business Management, 1987)
Corporate growth through mergers and acquisitions is strategy adopted by many South African companies to achieve their growth objectives. However, research in both the United Kingdom and the United States of America has found that most mergers and acquisitions do not meet expectations. Many fail and are divested, at considerable human and financial cost. To date, little research on the viability of growth through mergers and acquisitions has been done in South Africa. In the light of this, in-depth interviews were recently held with 20 senior South African executives, concerning the practices adopted by their organizations in the execution of mergers and acquisitions. This article presents the findings of the research in three specific areas: the formulation of a merger and acquisition strategy; the formulation of an acquisition profile; and the viability and critical success factors in adopting a growth through mergers and acquisitions strategy. Broadly speaking, it was found that the sample interviewed had a good understanding of the acquisition profile, but tended to be less focused in their reasons why their organizations elected to pursue a growth through merger and acquisition strategy. In addition, mergers or acquisitions seem to be more successful in the South African context than in other countries, where similar research has been conducted. A number of reasons for success or failure enumerated in the literature were confirmed. The main finding was that corporate growth through mergers and acquisitions can be either a viable strategy or road to ruin. Companies that systematically plan and manage their merger or acquisition programmes are likely to be successful; ad hoc approaches are likely to fail. The article provides aspects of a framework within which such a merger or acquisition programme may be structured to ensure success.
Keywords: 650